2021
DOI: 10.1177/1357633x20985763
|View full text |Cite
|
Sign up to set email alerts
|

The impact of telemedicine on patients with uncontrolled type 2 diabetes mellitus during the COVID-19 pandemic in Saudi Arabia: Findings and implications

Abstract: Introduction Routine diabetes care changed during the COVID-19 pandemic due to precautionary measures such as lockdowns, cancellation of in-person visits, and patients’ fear of being infected when attending clinics. Because of the pandemic, virtual clinics were implemented to provide diabetes care. Therefore, we conducted this study to assess the impact of these virtual clinics on glycaemic control among high-risk patients with type 2 diabetes mellitus (DM). Methods A prospective single-cohort pre-/post teleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 35 publications
1
51
0
3
Order By: Relevance
“…For the majority of patients (64%), only one or two visits were required during the 4-month study period. 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the majority of patients (64%), only one or two visits were required during the 4-month study period. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Research on the use of telepharmacy for diabetic patients during the COVID-19 pandemic is still very limited. The only study results the authors obtained were Tourkmani et al 32 The study showed positive results with the provision of interventions by a multidisciplinary team led by pharmacists. Another study on the use of telepharmacy during the COVID-19 pandemic in outpatients is conducted by Poderoso et al 38 showed that the patients get clinical follow-up and therapeutic adherence monitoring with free home delivery of medication reducing outpatient visits by 56%, the average patient visit before the pandemic was 215 ± 25 and the average visit during a pandemic after telepharmacy implemented was 95 ± 29.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in such situations in the future, technology and telemedicine should be used to fill the gaps when the healthcare system is overloaded [ 58 , 73 ]. A recent study from Saudi Arabia stated a significant progressive effect of telemedicine care on glycaemic control among high-risk patients with diabetes during the COVID-19 pandemic [ 74 ]. As of August 2020, a report indicated that almost 60,000 patients with diabetes benefitted from remote consultation in Saudi Arabia [ 75 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…[30][31][32] Before the pandemic, many studies indicated the clinical effectiveness of telemedicine in diabetes care, including significant and clinically relevant reductions in HbA1c. [31][32][33][34][35][36][37][38] Moreover, during the COVID-19 pandemic, two studies from Japan 39 and Saudi Arabia 40 reported similar positive clinical outcomes in terms of glycemic control. In addition, it has been shown that increasing patient contact through frequent phone calls improves patient therapy adherence, motivation, and metabolic control.…”
Section: Introductionmentioning
confidence: 99%